PENERIMAAN BUKU SEKOLAH ELEKTRONIK (BSE) PADA SMA di JAKARTA MENGGUNAKAN PENDEKATAN TECHNOLOGY IN ACCEPTANCE MODEL - Priatno Priatno (Institut Bisnis dan Informatika Kwik Kian Gie, 2016)
Electronic School Books (BSE) is a container support for the Program Bulk Cheap Textbook Lessons, through the National Agency for Education Standards (BSNP), with 942 titles on the link http://bse.depdiknas.go.id. Technology in Acceptance Model (TAM) proposed by Davis, regarding the use of information technology to the perceived ease and perceived usefulness of using statistical data analysis of Structural Equation Modelling (SEM) and software Analysis of Moment Structure (Amos). Electronic School Book Receipts (BSE) is determined by convenience variable (Perceived Ease of Use) and by variable efficacy (Perceived Usefulness), influence on attitudes to use (Attitude Towards Using), increasing the use of (Intention to Use), further increasing the usage of real systems (Actual System Usage).Â Keywords: Electronic School Books (BSE), Technology Acceptance Model (TAM), Structural Equation Modelling (SEM)